Case report: A proposed role for cardiopulmonary exercise testing in detecting cardiac dysfunction in asymptomatic at-risk adolescents - Edwards, Timothy; Tas, Emir; Leclerc, Kenneth; Børsheim, Elisabet (Frontiers in Pediatrics, 2023)
Noninvasive cardiopulmonary exercise testing (CPET) provides the valuable capacity to analyze pulmonary gas exchange and cardiovascular responses that can be used to differentiate normal cardiopulmonary responses from abnormal. This case report highlights a proposed role for CPET in identifying potential cardiac pathologies in at-risk adolescents. An abnormal CPET response in an asymptomatic adolescent revealed a family history of early-age CAD. The significance of the abnormal CPET response was further supported by the presence of an elevated concentration of circulating high sensitivity C-reactive protein (hs-CRP). These findings emphasize the importance of a thorough clinical evaluation in at-risk adolescents, as CPET can aid in the early detection and management of cardiac pathologies, especially when combined with other relevant biomarkers such as plasma hs-CRP concentration, which can further suggest underlying pathology. Management considerations using serial CPET evaluations are recommended. Thus, CPET abnormalities combined with elevated hs-CRP should be taken seriously and provide justification for further evaluation and monitoring in adolescents at risk for cardiovascular disease.